2011
DOI: 10.1002/14651858.cd003626.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids for primary sclerosing cholangitis

Abstract: BackgroundPrimary sclerosing cholangitis is a progressive chronic cholestatic liver disease that usually leads to the development of cirrhosis. Studies evaluating bile acids in the treatment of primary sclerosing cholangitis have shown a potential benefit of their use. However, no influence on patients survival and disease outcome has yet been proven. ObjectivesTo assess the beneficial and harmful e ects of bile acids for patients with primary sclerosing cholangitis. Search methodsWe searched The Cochrane Hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 78 publications
1
41
1
3
Order By: Relevance
“…However, in PSC, the effectiveness of these endoscopic procedures is still unclear because there have been no randomized controlled studies to report on the benefits (9). Some studies have reported that UDCA improved liver function, but they failed to demonstrate if it halted PSC progression (14)(15)(16). Furthermore, recent studies revealed that high-dose UDCA (28∼30 mg/kg/day) did not improve patient survival and was associated with severe adverse effects (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…However, in PSC, the effectiveness of these endoscopic procedures is still unclear because there have been no randomized controlled studies to report on the benefits (9). Some studies have reported that UDCA improved liver function, but they failed to demonstrate if it halted PSC progression (14)(15)(16). Furthermore, recent studies revealed that high-dose UDCA (28∼30 mg/kg/day) did not improve patient survival and was associated with severe adverse effects (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Higher doses of UCDA (20-30 mg/kg/day) have been shown to be detrimental, rather than to have any substantial clinical benefit [72][73][74][75][76]. UCDA does not improve liver histology or liver transplant free survival, nor does it prevent the development of cholangiocarcinoma, colonic adenomas, colon cancer or incidence of death [73,[77][78][79]. Corticosteroids have not been proven effective either as single agents or when used with colchicine or ursodeoxycholic acid [80], nor have methotrexate, colchicine, pentoxifylline, etanercept, or mycophenolate mofetil proved useful in PSC [81][82][83][84][85][86].…”
Section: Management Of Pscmentioning
confidence: 99%
“…Unatoč vrlo ograničenim dokazima za bilo kakvu učinkovitost navedene terapiju u pacijentica s PBC-om, utvrđeno je da značajno veći broj ispitanika prekida navedenu terapiju zbog nuspojava (RR 5,26; 95 % CI 1,26 do 22,04). 11,12 Naša je skupina autora objavila dva Cochrane sustavna pregleda na temu primarnog sklerozirajućeg kolangitisa. U prvom je analizirana primjena glukokortikoida, dok su u drugom obuhvaćene studije primjene žučnih kiselina kao terapijske opcije.…”
Section: Kolestatske Bolesti Jetreunclassified